EXPLORING THE HOME AND SCHOOL BASED STRATEGIES FOR CHILDREN WITH CEREBRAL PALSY: A PHENOMENOLOGICAL STUDY - Amber Baseer; Majeed, Asma; Nazir, Arooj; Khawar, Rabia (Journal of Pakistan Psychiatric Society, 2022)
OBJECTIVE The  present  study  aimed  to  explore  the  strategies  which  can  be  used  by  parents  and teachers  to  facilitate  their  CP  child  at  home  and  school.STUDY DESIGNPhenomenology  research  design  was  adopted  for  this  research. PLACE AND DURATION OF THE STUDYParticipants  were  recruited  from  special  education  schools  of  Lahore  over  a  period  of  6 months  from  August  2018  to  February  2019.SUBJECTS AND METHODSThe  sample  of  this  study  comprised  of  six  child  psychologists  working  with  CP  children. For  the  present  study  six  in-depth  interviews  were  conducted  with  psychologists.  After  the  in-depth  interviews  were  conducted  they  were  transcribed  in  Urdu.  Interpretive Phenomenological  analysis  was  used  to  analyze  the  data.  RESULTSTwo  set  of  themes  emerged  from  the  analysis  which  included  the  strategies  that  can  be  used  by  parents  and  teachers  to  facilitate  their  CP  child  at  home  and  school.CONCLUSION The  findings  of  the  study  also  highlighted  the  strategies  that  can  be  used  by  teachers  and  parents  to  provide  a  better  environment  to  the  children  with  Cerebral  Palsy.  Separate  strategies  for  parents  and  teachers  were  suggested.  The  parental  strategies  theme  further  have  five  sub-ordinate  themes  namely;  attitude  of  parents, attitude  of  siblings, attitude  of  extended  family, home  environment and home  based  interventions.  The teacher  level  strategies  further  has  nine  sub-ordinate  themes namely; attitude  of  teachers, attitude  of  class  fellows, teaching  techniques, curriculum  modifications, classroom  modifications, use  of  assistive  technology, vocational  training, collaborative  team  work and counseling.